Assessing non-linearities and heterogeneity in debt sustainability analysis: Panel spline approach - Benjamin Owusu; Bettina Bökemeier; Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2021)
This paper empirically studies public debt sustainability with the penalized panel splines approach for 25 EU economies from 2000 to 2019 by estimating the response of the primary surplus to lagged debt relative to GDP, respectively. A positive coefficient on average indicates sustainable policies, which is supported by all our results. Moreover, we show that this relationship is not homogeneous across the distribution of the debt ratios, but, varies with the magnitude of public debt to GDP. The estimations reveal a strongly increasing reaction for small and high debt ratios while it is rather flat for intermediate levels. This holds for normal times, too, whereas during years of economic crises a monotonously increasing response can be observed. Additionally, for a cluster consisting of smaller EU economies, there is indication of "fiscal fatigue", meaning that the effort of active fiscal counter-steering peters out for high ratios of public debt to GDP. The same effect can be observed for the whole sample and for a sample including the large EU economies, once Greece is removed.
urn:nbn:de:0070-pub-29548606
Keywords: H63; E62; 330; Debt sustainability; fiscal response function; panel spline estimation